AL-USHÛL AL-‘ARABIYYAH LI ASMÂ AL-ISYÂRAH FÎ LUGHÂT AL-‘ÂLAM MIN MANZHÛR NAZHARIYYAH JADZR AL-KALIMAH - Zaidan Ali Jassem (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2018)
This paper aims to establish the Arabic cognates or origins of "demonstrative pronouns" in the world languages from a radical consonantal (lexical root) theory perspective. The data comprises key demonstrative pronouns like this, that in eleven major and minor families like Indo-European, Sino-Tibetan, Afro-Asiatic, Austronesian, Dravidian, Turkic, Mayan, Japonic, Niger-Congo, Uto-Aztec, and Tai-Kadai, which make up 60% of world languages and 96% of world population. The results showed that all such demonstrative pronouns have true Arabic cognates with the same or similar forms and meanings. Therefore, the results support the adequacy of the radical consonantal or lexical root theory according to which, unlike the Comparative Method and/or Family Tree Model, all world languages are related to one another. Thus, Arabic can be safely said to be the radical language itself to which all languages can be related for sharing demonstrative pronouns with all languages and for having a huge phonetic, morphological, grammatical, and lexical repertoire.